Looking Forward and Looking Backward: Cognitive and Experiential Search - Gavetti, Giovanni; Levinthal, Daniel (Administrative Science Quarterly, 2000)
We used computer simulations to examine the role and interrelationship between search processes that are forward-looking, based on actors' cognitive map of action-outcome linkages, and those that are backward-looking, or experience based. Cognition was modeled as a simple, low-dimensional representation of a more complex, higher dimensional fitness landscape. Results show that, although crude, these representations still act as a powerful guide to initial search efforts and usefully constrain the direction of subsequent experiential search. Changing a cognitive representation itself can act as an important mode of adaptation, effectively resulting in the sequential allocation of attention to different facets of the environment. This virtue of shifting cognitive representation, however, may be offset by the loss of tacit knowledge associated with the prior cognition.